Efficient and secure communication scheme for OFDM system based on physical layer non‐reconciled keys - Song, Xuanyan; Jin, Liang; Huang, Kaizhi; Xiao, Shuaifang; Sun, Xiaoli; Zhao, Jianlei (IET communications, 2022)
The secure communication scheme based on physical layer non‐reconciled keys receives extensive attention due to its high encryption rate. However, the mismatched secret bit sequences between the two users leads to higher BER and lower coding efficiency for this type of scheme. To solve this problem, this paper proposes an efficient and secure communication scheme for OFDM system with non‐reconciled keys. Initially, an adaptive coding method is designed to encode information blocks with different code rates to improve the overall efficiency. Then, on this basis, a sorting xor encryption algorithm is designed to reduce the bit error rate by sorting the channel estimation value and mapping them to corresponding sub‐channels. Theoretical analysis and simulation results indicate that this scheme can effectively reduce the bit error rate and improve the efficiency of information coding compared to the existing method.